How Genes Matter: Genetic Medicine as Subjectivisation Practices - Wieser, Bernhard (transcript, 2017)
Understanding the significance of genetic factors for our lives requires an analysis that goes beyond biological aspects. It is especially necessary to take into account how human beings relate to others and to themselves. Who we are is a result of social action and the ways in which human beings constitute themselves as subjects. Seen from this perspective, genetic medicine is a social practice that shapes how we think about us, how we conduct our behaviour and how we care for our children.This book scrutinises practices by which individuals become knowledgeable about their genes and constitute them as responsible decision makers.